EVALUATION OF EARLY TREATMENT OF IDIOPATHIC CLUBFOOT USING THE PONSETI METHOD - CAIO LUIZ DE TOLEDO OLIVEIRA; GERALDO MOTA GONÇALVES FILHO; JOSÉ BATISTA VOLPON (Acta Ortopédica Brasileira, 2023)
ABSTRACT Congenital clubfoot is one of the most common congenital deformities of the lower limbs, with an estimated incidence of 1 for every 1,000 live births. Its treatment is controversial, and currently the Ponseti method has been widespread, showing promising results and decreasing the need for extensive surgical releases, as was usually done until the introduction of the technique. Currently used in approximately 55 countries, the method has changes and scopes that vary according to the society in which it is applied, with the results and peculiarities of the method molded according to the sample studied. Objective: To evaluate the clinical outcome of clubfoot treatment using the Ponseti method under local conditions. Methods: The clinical evaluation will include a descriptive analysis of the sample, as well as radiographic evaluation and family satisfaction with the treatment. Results: In total, 46% of the patients had good results and no family was dissatisfied with the treatment results. No statistically relevant relationships were found between the studied variables. Conclusion: The results are good and generally similar to those in the literature. Our epidemiological data generally agree with those reported by other authors. Level of Evidence IV, Case Series.